Kelayakan Finansial dan Adaptasi Bisnis Pengelolaan Food Waste Berbasis Biokonversi Hermetia Illucens di TPS 3R Mutiara Bogor Raya - Dandi Rivaldi Sudradjat (Bekasi Development Innovation Journal, 2023)
The high amount of waste in Indonesia is a serious problem, one of which is food waste which can be pursued by processing based on the bioconversion of Hermetia Illucens or the Latin name of Black Soldier Fly (BSF) in the maggot phase which produces economic value. Mutiara Bogor Raya (MBR) 3R TPS is a 3R TPS that has implemented the bioconversion of waste processing but is still constrained by financial problems. This study aims to analyze the financial feasibility of managing household food waste based on BSF maggot bioconversion in TPS 3R MBR, the benefits and social costs of the existence of TPS 3R MBR, and the financial feasibility of the planned development of TPS 3R MBR. This study uses primary and secondary data by combining methods of financial feasibility analysis, cost benefit analysis, and scenario analysis. The results of this study indicate that household food waste management based on maggot bioconversion BSF TPS 3R MBR is feasible to run. The perceived social benefits outweigh the social costs. The plan to develop TPS 3R MBR is feasible to be realized by using an incinerator scheme, increasing employee wages by 10%, and the final product in the form of dried maggot BSF.